The Representation of Gender Equality in The Illustration of English Textbooks for Senior High School - Dian Eka Handayani; Lita Tungka (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2023)
This research focuses on the representation of gender equality in two English textbooks for eleventh-grade students in senior high school. Textbooks are crucial educational resources that shape students' understanding, and illustrations play a significant role in engaging students and shaping their mindsets. The study analyzes English textbooks from the government (textbook K) and one private publisher (textbook P) to assess the representation of gender in their illustrations. The findings reveal that textbook K already promotes gender equality in the sense of a balanced representation of male and female illustrations and the use of both genders in illustrating leisure activities. However, gender bias persists in both books, highlighting the need to address this issue and strive for a balanced representation of gender. Further research is recommended to explore gender equality in illustrated figures across different grade levels and to investigate gender-related issues in a broader range of English textbooks.